Sudan low changes affecting rainy days in southwestern Iran over six decades (1957–2019). Issue 2 (11th December 2021) - Mohammadi, Fahimeh; Pazhoh, Farshad; Hombari, Farzaneh Jafari
Abstract: The present study evaluated the dynamic changes in Sudan low systems over six decades (1957–2019), which were classified based on solar cycles. Rainfall days were extracted in January using data from 42 synoptic stations in the south and southwest regions of Iran. Then, the rainy days due to the Sudan low system were separated from the precipitation of the other atmospheric systems using the visual analysis of the maps. The synoptic analysis indicated that the sea level pressure has been decreasing at all sampling stations from the first to the sixth decade. Furthermore, decreasing elevation to −80 m (negative anomaly) in the 500 hPa level atmosphere from the first decade to the sixth decade indicated further atmospheric instability and more strengthening of the Sudan low compared to previous decades. The contribution of advection moisture to the area increased within the region at 700 hPa. This implies that the role of the transferred moisture from the intertropical convergence zone is increasing in the systems transferred from Sudan and in the study area. In general, the share of Sudan low precipitation is increasing in the south and southwest regions of Iran. This result is a positive effect of the climate change on the study area. HIGHLIGHTS: This study describes the decadal changes in Sudanese low pressure affecting precipitation days in southwestern Iran. Sea level pressures have been declining from the first decade to the sixth decade. Sudan low pressure has intensified over the period under review. The share of Sudan low pressure in the abundance of rainy days in the southern and southwestern regions of Iran is increasing. Graphical Abstract